An aerobic copper-mediated domino process for the synthesis of 3-(trifluoromethylseleno)indoles. Issue 10 (25th February 2022) - Wang, Hui; Yao, Yunfei; You, Yi; Huang, Yangjie; Weng, Zhiqiang
Abstract : An aerobic copper-mediated domino reaction for the synthesis of 3-(trifluoromethylseleno)indoles by trifluoromethylselenolation of N -Ts 2-alkynylaniline with [(bpy)CuSeCF3 ]2 is described. Abstract : An aerobic copper-mediated domino reaction for the synthesis of 3-(trifluoromethylseleno)indoles by trifluoromethylselenolation of N -Ts 2-alkynylaniline with [(bpy)CuSeCF3 ]2 is reported. This reaction proceeds through sequential oxidation, alkyne coordination, and deprotonation followed by reductive elimination. This mild and robust method is highly functional group tolerant and provides straightforward access to 3-(trifluoromethylseleno)indoles in moderate to good yields.